Description of two new species of the genus Aleuropleurocelus Drews & Sampson (Hemiptera: Aleyrodidae) from Mexico - Sánchez-Flores, Oscar Ángel; Carapia-Ruiz, Vicente Emilio (Instituto de Ecología, A.C., 2018)
Aleuropleurocelus caudatus Sánchez-Flores and Carapia-Ruiz sp. nov. collected in Asunción Ixtaltepec, Oaxaca from the underside of leaves of Coccoloba uvifera, and Aleuropleurocelus bidentatus Sánchez-Flores and Carapia-Ruiz sp. nov. collected in Acapulco, Guerrero from the underside of leaves of Diospyros acapulcensis subsp. acapulcensis are described and illustrated. Figures of morphological structures of the puparia are provided, and differences from other Aleuropleurocelus species are discussed.